Motiv Rdeče kapice v kratki sodobni pravljici Rdeče jabolko Svetlane Makarovič in Kaje Kosmač - Lackner, Tadeja (Jezik in slovstvo, 2011)
With her fairy tales, writer Svetlana Makarovič addresses both child readers and adult readers. The short contemporary fairy tale Rdeče jabolko was published in 2008 by the Centre for Slovenian Literature. The initiative to produce Rdeče jabolko came from Kaja Kosmač, who was the book's co-author, as well as being its illustrator and designer. The authors addressed the work to adult readers and mature youth readers. Rdeče jabolko is intertextually linked with the motive of Little Red Riding Hood, which in the ATU index of fairytale types is labelled with the number ATU 333 (Hans Jörg Uther 2004: 224). This motive can be found in the past in many cultures. The present discussion focuses on a version from the oral tradition from the 11th century, as well as on the variants of Little Red Riding Hood by Charles Perrault from 1697 and those by the brothers Grimm from 1812-1815 and 1857.
Keywords: Makarovič, Svetlana, 1939-; Kosmač, Kaja, 1978-; slovenska mladinska književnost; pravljice; kratka sodobna pravljica; motiv Rdeče kapice; simboli; symbol; socializacija; socialization